A political theory of rights - Ingram, Attracta (Clarendon Press ; Oxford Univ. Press, 1994)
Rights are the basic building blocks of every liberal state. This book addresses fundamental questions about them. What are they? How can they be justified? What role should they play in political life? By offering new and cogent answers to these questions, the book aims to provide a firm foundation for notions such as human rights.